PANCASILA PENGENDALI BISNIS WARALABA - Sitti Maryam (Cross-border, 2022)
Pancasila as a way of life, philosophy and ideology of the Indonesian people, so it is natural and proper to be a strong pillar in running a franchise business. The basic values ​​of Pancasila that are applied in regulating the economy, including franchise businesses, are oriented to the values ​​of God, humanity, unity, democracy and social justice, as contained in Article 33 paragraph (4) of the 1945 Constitution, which is further elaborated in Government Regulation Number 16 of 1997 concerning Franchising, followed by Decree of the Minister of Industry and Trade of the Republic of Indonesia (SK.MPP) Number 259/MPP/Kep/7/1977 concerning Provisions and Procedures for Implementing Franchise Business Registration. Then issued the Government Regulation of the Republic of Indonesia Number 42 of 2007 concerning Franchising. In addition, both parties (the grantor and the franchisee) are bound by an agreement made and mutually agreed upon. This study uses qualitative research methods accompanied by descriptive analysis by referring to some literature that questions the problem of the object under study. The government must be able to have a positive influence on global economic development, as well as anticipate the effects of globalization, and prevent monopolistic practices and business competition in running a franchise business.